Carrapatos infestando pequenos roedores silvestres em três municípios do estado de São Paulo, Brasil - Martins, Thiago Fernandes; Peres, Marina Gea [UNESP]; Costa, Francisco Borges; Bacchiega, Thais Silva [UNESP]; Appolinario, Camila Michele [UNESP]; Antunes, João Marcelo Azevedo de Paula [UNESP]; Vicente, Acácia Ferreir [UNESP]; Megid, Jane [UNESP]; Labruna, Marcelo Bahia (FapUNIFESP (SciELO), 2016)
From May to September 2011, a total of 138 wild rodents of the Cricetidae family were collected in the cities of Anhembi, Bofete and Torre de Pedra, in São Paulo State. All animals were examined for the presence of ticks, which were collected and identified at species level in the laboratory by morphological examination (for adults, nymphs and larvae) and molecular biology, by sequencing of a fragment of the 16S mitochondrial rDNA (for larvae). A total of 47 ticks (21 larvae and 26 nymphs) were collected from rodents, identified as 21 larvae and 23 nymphs of Amblyomma ovale (collected on Oligoryzomys nigripes, Oligoryzomys flavescens, Sooretamys agouya and Nectomys squamipes), two nymphs of Ixodes schulzei (O. nigripes and O. flavescens) and an Amblyomma sculptum nymph in S. agouya. The overall prevalence of parasitism by A. ovale was 4.3% for larvae, and 10.1% for nymphs. The mean intensity of parasitism was 3.5 larvae/ parasitized animal, and 1.6 nymphs/parasitized animal. One O. nigripes was found parasitized by both larva and nymph of A. ovale, and another O. nigripes was parasitized simultaneously by an I. schulzei nymph and five A. ovale nymphs. This research reports the following unpublished records: A. ovale on O. flavescens, O. nigripes and S. agouya; A. sculptum on S. agouya; and I. schulzei on O. flavescens and O. nigripes.
Ticks infesting wild small rodents in three areas of the state of São Paulo, Brazil
Keywords: Amblyomma ovale; Amblyomma sculptum; Brazil; Ixodes schulzei; Ticks; Wild rodents